Formulasi dan Uji Aktivitas Antibakteri Gel Minyak Atsiri Rimpang Lengkuas Merah (Alpinia purpurata K. Schum) terhadap Propionibacterium acnes - Astriani Natalia Br Ginting; Vera Estefania Kaban; Roy Indrianto Bangar; Daimah W. S. Harahap (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Acne is a common dermatological condition caused by the bacterial infection of Propionibacterium acnes, leading to skin inflammation. Red galangal (Alpinia purpurata K. Schum) is known to exhibit antibacterial activity due to its essential oil content, flavonoids, and alkaloids. This study aims to formulate and evaluate the antibacterial activity of a gel preparation based on red galangal rhizome essential oil against Propionibacterium acnes. The research follows a laboratory experimental design, including the extraction of red galangal rhizome essential oil via maceration, formulation of the gel, and evaluation of its physical properties, such as pH, homogeneity, spreadability, and antibacterial activity using the disc diffusion method. The results demonstrated that the gel formulation met the required physicochemical standards, with a pH ranging from 6.4 to 6.8, good homogeneity, and an optimal spreadability of 5–7 cm. The antibacterial test revealed a significant inhibitory effect against Propionibacterium acnes, with an inhibition zone of up to 11.24 mm at a 15% concentration. These findings suggest that red galangal rhizome essential oil possesses strong antibacterial potential, making it a promising candidate for natural topical acne treatment. In conclusion, the red galangal essential oil gel exhibits favorable antibacterial activity against Propionibacterium acnes and has potential as an alternative acne treatment. Further studies are necessary to enhance the stability and efficacy of the formulation for optimal clinical applications.